Engineered Strategies for Lipid Droplets-Targeted AIEgens Based on Tetraphenylethene - Fei Zhang; Yao Zhang; Zhuoxia Li; Xiaoxiao Wu; Dong Wang; Youling He; Hong Cheng; Baolei Fan; Dan Zhu; Min Li; Ben Zhong Tang (Molecules)
Lipid droplets (LDs), once regarded as inert fat particles, have been ignored by scientific researchers for a long time. Now, studies have shown that LDs are dynamic organelles used to store neutral lipids in cells and maintain cell stability. The abnormality of intracellular LDs usually causes metabolic disorders in the body, such as obesity, atherosclerosis, diabetes, and cancer, so the LDs have attracted wide attention. The traditional small molecules used for LDs recognition seriously affect the imaging effect due to their poor photo-stability, low signal-to-noise ratios, and aggregation-induced quenching (ACQ). In contrast to ACQ, aggregation-induced emission (AIE) materials, with structural modifiability, can make up for the aforementioned deficiencies in the field of fluorescence imaging and have attracted much attention. In this review, the importance of LDs in vivo, the design principles for LDs recognition, and the recent research progress of AIE compounds with tetraphenylethene (TPE) structure in LDs targets are reviewed. We expect this review to further provide researchers with feasible methods and protocols for expanding LDs identification, imaging, and other applications.